2019
DOI: 10.1002/asia.201900154
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Communication between S=1/2 Spins in Negatively‐charged Double‐caged Fullerene C60 Derivative Bonded by Two Single Bonds and Pyrrolizidine Bridge

Abstract: Radical anion salt {cryptand[2.2.2] (K + )} 2 (bispheroid) 2À ·3.5C 6 H 4 Cl 2 (1)o ft he double-caged fullerene C 60 derivative,i nw hich fullerene cages are linked by a cyclobutane bridging cycle and additionally by ap yrrolizidine moiety,w as obtained. Each fullerenec age in this derivative accepts one electron on reduction, thus forming the (bispheroid) 2À dianionsw ith two interacting S = 1/2 spins on the neighboring cages. Low-temperature magnetic measurements reveal as inglet ground state of the bispher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Salts 1 and 2 are EPR silent and, therefore, diamagnetic in the whole studied temperature range. It should be noted that organic compounds with triplet (S = 1) state always show characteristic EPR signals, [45][46][47] and the absence of these signals in 1 and 2 up to 295 K clearly show that the obtained H 2 TPyzPzR 8 2À (R = Et, Me) dianions have singlet (S = 0) ground state and triplet state is not populated up to 295 K. Previously, it was also shown that H 2 TPyzPz 2À dianions are EPR silent and diamagnetic whereas EPR spectra of the H 2 TPyzPz À radical anions contain an intense narrow signal with g = 2.0025-2.0061 and the linewidth DH = 0.44-0.59 mT. 29 Moreover, the singlet ground state for the H 2 TPyzPz 2À dianions was shown by DFT calculations (the singlet-triplet energy gap was calculated to be 1130 K).…”
Section: (D) Magnetic Propertiesmentioning
confidence: 99%
“…Salts 1 and 2 are EPR silent and, therefore, diamagnetic in the whole studied temperature range. It should be noted that organic compounds with triplet (S = 1) state always show characteristic EPR signals, [45][46][47] and the absence of these signals in 1 and 2 up to 295 K clearly show that the obtained H 2 TPyzPzR 8 2À (R = Et, Me) dianions have singlet (S = 0) ground state and triplet state is not populated up to 295 K. Previously, it was also shown that H 2 TPyzPz 2À dianions are EPR silent and diamagnetic whereas EPR spectra of the H 2 TPyzPz À radical anions contain an intense narrow signal with g = 2.0025-2.0061 and the linewidth DH = 0.44-0.59 mT. 29 Moreover, the singlet ground state for the H 2 TPyzPz 2À dianions was shown by DFT calculations (the singlet-triplet energy gap was calculated to be 1130 K).…”
Section: (D) Magnetic Propertiesmentioning
confidence: 99%
“…The formation of C 60 •– shifts the F 1u (4) mode to 1390–1396 cm –1 . Notably, the spectrum of pristine C 60 exhibits only four IR-active modes owing to the suppression of many symmetry-forbidden modes in C 60 . As discussed earlier, both dimerization and coordination of C 60 decrease its symmetry.…”
Section: Resultsmentioning
confidence: 79%
“…Therefore, additional coordination of two Fe­(CO) 2 provides closer approach of fullerenes in the dimers . Previously, the formation of doubly bonded (C 60 ) 2 dimers was found through the coordination of two Co­(dppe) fragments as bridges or by introducing organic bridges to the C 60 cages . Additionally, in 1 , each iron atom coordinates two carbonyl groups, resulting in a coordination number of six for iron.…”
Section: Resultsmentioning
confidence: 99%
“…Fullerene radicals with alkyl or hydrogen substitutions can dimerize to form singly-bonded 4,4′-disubstituted adduct [ 41 ]. The electrochemistry of fullerene and fullerene dimers is of particular interest, as the redox behavior of dimeric fullerenes reflects the electronic interaction between the fullerene cages [ 42 , 43 , 44 ]. Potential values are essential for understanding and predicting the homogeneous redox properties of each particular fullerene derivative, as well as the areas of their possible application.…”
Section: Introductionmentioning
confidence: 99%